2020
DOI: 10.1136/jitc-2020-001066
|View full text |Cite
|
Sign up to set email alerts
|

Subtype and grade-dependent spatial heterogeneity of T-cell infiltration in pediatric glioma

Abstract: Brain tumors are the leading cause of cancer-related mortality in children and have distinct genomic and molecular features compared with adult glioma. However, the properties of immune cells in these tumors has been vastly understudied compared with their adult counterparts. We combined multiplex immunofluorescence immunohistochemistry coupled with machine learning and single-cell mass cytometry to evaluate T-cells infiltrating pediatric glial tumors. We show that low-grade tumors are characterized by greater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 30 publications
6
32
0
Order By: Relevance
“…Immune classification was also correlated with somatic mutations, copy number alterations, and molecular pathways related to tumorigenesis, metabolism, and immune responses [ 61 ]. The finding that LGGs are characterized by greater immune cell infiltration, especially T cells, compared to HGGs are in line with other publications [ 17 ]. However, even among LGG, T cell infiltration was highly variable and subgroup-dependent, with greater T cell density in pleomorphic xanthoastrocytoma (PXA) and ganglioglioma (GG) [ 17 ].…”
Section: Targeting Immune Cells In Pediatric Brain Tumorssupporting
confidence: 92%
See 1 more Smart Citation
“…Immune classification was also correlated with somatic mutations, copy number alterations, and molecular pathways related to tumorigenesis, metabolism, and immune responses [ 61 ]. The finding that LGGs are characterized by greater immune cell infiltration, especially T cells, compared to HGGs are in line with other publications [ 17 ]. However, even among LGG, T cell infiltration was highly variable and subgroup-dependent, with greater T cell density in pleomorphic xanthoastrocytoma (PXA) and ganglioglioma (GG) [ 17 ].…”
Section: Targeting Immune Cells In Pediatric Brain Tumorssupporting
confidence: 92%
“…However, recent efforts have shown that antitumor immune control exists in pediatric brain tumors, e.g., rhabdoid tumors and LGG showed strong T cell infiltration [ 15 , 16 , 17 ]. Moreover, several studies present prognostications of specific immune cell infiltrates on overall survival [ 18 , 19 , 20 , 21 , 22 ] ( Table 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…We believe that more papers focused on tumor characterization and technical factors would be useful in this regard. On the one hand, although heterogeneity itself was proposed as a biomarker in the past [ 346 , 347 ] it has been reported that heterogeneity is related to biological characteristics such as tumor microenvironment [ 348 , 349 ], genetic expression [ 350 ] and, macroscopically, tumor grades or cancer subtypes [ 351 ]; thus, linking radiomic features with particular biological characteristics could provide additional evidence for the field. On the other hand, further work is still needed to evaluate the impact of image acquisition, reconstruction, post-processing and feature calculation [ 352 ].…”
Section: Discussionmentioning
confidence: 99%
“…The deep profiling capabilities of mass cytometry is also elucidated in the potential to profile the phenotype of brain tumor initiating cells in the context of GBM [ 76 ], while the combination of MC with RNA-seq has allowed the mapping of cellular states of microglia, providing valuable information in the context of how gliomagenesis may occur [ 77 ]. Recent applications of MC have contributed towards the role of the microenviroment in CNSM homeostasis as well as towards the development of immunosuppressive phenotypes, which are distinct depending on the tumor type [ 78 , 79 , 80 , 81 , 82 ].…”
Section: Phenotypic Analysismentioning
confidence: 99%